Spiritual Care Nurse To Patient With Breast Cancer At Last Stage : a Literature Review - Nurul Rezki Anisa; Kadek Ayu Erika; Rini Rachmawaty (Interest : Jurnal Ilmu Kesehatan, 2020)
Background: Spiritual care is one of the strategies for managing care towards the end of life in the hospital as mentioned in the Nursing Intervention Classification. Aim this study is to describe spiritual care nurse to patient with breast cancer at last stage. Methods: A literature review were obtained from PubMed, and google scholar using the keywords breast cancer AND palliative care and breast cancer AND spiritual care by adding filters: the type of article is Full text with Randomized Controlled Trial, published in the last 5 years, written in English and Indonesian, human studied, specific to cancer, and are in the category of nursing journals and MEDLINE. Result: According to a review of existing research, spiritual care is effective to overcome psychological problems, such as anxiety, stress, or depression as it affects patients to solemnly accept their health condition including the complications in positive ways. Therefore, patients receiving spiritual care will be more adhere to their medical treatments, will have lack of emotional disturbances and substance abuse, have greater social support, will be more frequent performing their health behavior and have a longer period of survival.Conclusion: Spiritual care is highly needed in medical care, especially for those who have serious and life-threatening diseases. Assessing and addressing the spiritual needs of patients is associated with greater satisfaction with care, better quality of life, less depression, less unnecessary health services, and better nurse-patient relationships.